П’ятницька церква у 1943-1963 рр. згідно з документами Державного архіву Чернігівської області - Нижник, Л. (Сiверянський лiтопис, 2017)
У статті на основі документів Державного архіву Чернігівської області розповідається, як реставрували П’ятницьку церкву в 1943-1963 роках, які труднощі
спіткали реставраторів, як планували відновити дзвіницю та збудували огорожу.
У статті надається довідка про кошти, які були витрачені на реставрацію пам’ятки архітектури. В статье на основе документов Государственного архива Черниговской области
рассказывается, как реставрировали Пятницкую церковь в 1943-1963 годах, какие
трудности препятствовали реставраторам, как планировали восстановить колокольню и построили ограду. В статье приводится справка о средствах, которые были истрачены на реставрацию церкви. In article on based of documents of the State Archives of Chernihiv region tells how restored
the church of St.Paraskeva Pyatnitsa in 1943-1963gg., what difficulties befell restorers: not
enough construction materials and labor hands. According to the project of P. Baranovsky
was planned to restore church, bell tower and build a fence, and then plans changed. And
local government representatives started writing letters to the Council of Ministers of the
UkranianSSR with request of allow to disassemble bell tower because it has no architectural
not historical value. Afterwards dismantled bell tower and fence.